The art of the steal - Sobol, Jonathan; Russell, Kurt; Dillon, Matt; Baruchel, Jay, 1982- (Beverly Hills, CA : Anchor Bay Entertainment, 2014)
A motorcycle daredevil and semi-reformed art thief teams up with his brother to steal a priceless historical book.
Originally released as a motion picture in 2013.
Wide screen 1.85:1.
Kurt Russell, Matt Dillon, Jay Baruchel, Kenneth Welsh, Chris Diamantopoulos.
MPAA rating: R.
In English with optional English or Spanish subtitles.
Keywords: Brothers -- Drama; Art thieves -- Drama; Fiction films; Thriller films; Feature films